Perempuan dan Diskriminasi: Analisis Permasalahan Buruh Tani di Pengalengan Bandung - Deni Sutisna; Dyah Indraswati (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2020)
Gender equality is a necessity that has not been maximized. Although it continues to be campaigned, however, many women are still found. This study aims to analyze the problems of female farm workers in Pangalengan Bandung and the factors that cause it. Assessed by descriptive method using interview and observation techniques. The result of the research shows that the problems which are often problems are economic problems, welfare problems, work comfort problems, and national problems. The basic forms of women include: gender in wage patterns between men and women, gender workload between men and women, and the view that women are weaker than men. Meanwhile, the main national cause is the strong patriarchal culture which is not aware that it is still attached to society. This research also finds a concept that the welfare level of female farm workers is not the same. This depends on their daily income. Some include prosperous agricultural laborers, almost prosperous farm workers, and less prosperous farm workers. These findings provide a different view from previous studies which state that agricultural labor is closely related to poverty.